PENGARUH KUALITAS PELAYANAN LOKET PENDAFTARAN TERHADAP KEPUASAN MASYARAKAT DI KANTOR PERTANAHAN KABUPATEN BOGOR - ., Muhlis; Rahmania, Dinar (Economicus, 2019)
The purpose of this study was to determine the effect of reliability, responsiveness, assurance, attention, and physical evidence on community satisfaction partially or simultaneously. The method of collecting data for testing hypotheses using filling in questionnaires aimed at 100 respondents of people over the age of 17 who use the services at the registration counter.The results of multiple linear analysis show that the influence of service quality dimensions is R2 = 0.346, which means that the contribution of variable X (Service Quality) plays a role in influencing the Y variable (Community Satisfaction) of 34.6%. Based on the results of the t test the responsiveness and attention variables influence people's satisfaction. Judging from the results of the test f community satisfaction together is influenced by variables of reliability, responsiveness, assurance, attention, and physical evidence at the level of alpha significance of 10% or 90% confidence level. Based on the results of the t test the responsiveness and attention variables influence people's satisfaction.